Beyond ASD: Evidence for the Effectiveness of Social Narratives. (September 2017) - Zimmerman, Kathleen N.; Ledford, Jennifer R.
Social narratives (e.g., Social Stories™) are common antecedent-based interventions promoted for the purposes of improving prosocial behaviors and reducing challenging behavior for children with and without disabilities. Although they are commonly prescribed and used, their effectiveness has almost exclusively been assessed for children with autism spectrum disorder (ASD). The purpose of this review was to synthesize the literature on social narrative interventions for children without ASD using a new synthesis framework: the Single Case Analysis and Review Framework (SCARF). Specifically, the review assessed the quality, rigor, and outcomes of single case design studies measuring the effectiveness of social narratives for decreasing challenging behavior or increasing prosocial behavior in children without ASD. Conclusions suggest cautious use of social narratives in isolation for children without ASD due to variable outcomes and absence of a sufficient number of rigorous studies. Future high-quality research is needed to address questions surrounding effective instructional components, participant characteristics, and implementation fidelity.